Evaluation of Breast cancer Treatment in AlHussein Hospital in Karbala city (A Descriptive Study) - Mohammed Abdullah, Amer; Kalaf Hassan, Abdulrazzaq (International Journal of Psychosocial Rehabilitation, 2020)
Background: breast conserving surgery provide good choice for treatment of stage 1 and II breast cancer and has equivalent out come in term of survival and prognosis. Aims of the Study: To evaluate breast cancer treatment according to multiple variables and patient’s wish in Alhussain hospital in Karbala city. Patient and methods: - The present study is considered as a descriptive study, which has been conducted at AI-Imam AI-Hussein medical city in Karbala governorate during the period from 1st September 2017 to the 30 of December 2018. Fifty-two patients included in the study were admitted to the general surgical ward. The entire patients were first visiting the breast clinic or general surgical out-patient clinic or private clinic, every case is assessed by triple assessment (history and clinical examination, imaging study, histological diagnosis). Each case was presented and discussed in MDT (multidisciplinary team), after that we do the operation (wide local excision) and the specimen without formalin send for the lab. unit in our hospital for diagnosis and assessment of the margins, the result usually come after 20-30 minutes. As the result come back, if the margins were free then we start with axillary dissection or we do re-excision if the margins were positive and then the wound closed with closed system drain after secure hemostasis, and the axillary dissection is standard to the level II L.N dissection. Results: Fifty-two patients with breast cancer included in our study, twenty three patients (44%) were treated by mastectomy and twenty nine patients (56%) were treated by breast conserving surgery. The most common type was invasive ductal carcinoma, which can be treated by either modality (breast-conserving surgery or mastectomy). A sentinel lymph node biopsy (S.L.N.B) is important to avoid negative axillary dissection. In conclusions, screening program for breast cancer to detect early disease is very important subject before proceeding to axillary dissection S.L.N.B is very important and useful. The choice of Mastectomy was lower than that of Breast Conserving Surgery in our study for early treatment with breast cancer.